La captatio testamentorum frente al derecho - Cuena Boy, Francisco (Tesserae iuris, 2023)
Assuming the real presence of the phenomenon in Roman society between the first century BC. and the second century AD., the captatio testamentorum is initially studied to establish its concept, define the profile of its protagonists –the captator and the captandus– and explain its operation. The material used essentially comes from a large number of literary sources of different nature: writings of moralists, historians, satirists, etc. A short allusion is then made to the different judgment that morality and law reserve, respectively, for the captator, and the cunning captandus who takes advantage of him. Finally, an attempt is made to establish the true legal significance of the captatio and its consequences as an effective impediment to testamentary freedom. This is done by putting the activity under study in relation with the concept of dolus malus and with the corresponding assumptions of D. 29.6 and C. 6.34.